Explaining the interactions of city and border with the sustainable development approach Based on the logic of fuzzy multi-criteria decision making Case study: Zahedan ,Mijaveh, Dost Mohammad, Khash and Saravan border towns,Sistan and Baluchestan Province. - reza mohammadi; zyinab karkaabadi; ghlam reza miri (تحقیقات کاربردی علوم جغرافیایی)
In this study, the actions and interactions between the city and the border were studied and explained. This research is applied in terms of purpose and in terms of descriptive-analytical method in library and field method. Data were collected through questionnaires and interviews. The statistical population consists of one percent of the population of border towns of Zahedan, Mirjaveh, Dost Mohammad, Khash and Saravan(N=8092). Using Cochran formula, 367 people were selected as the sample. Data were analyzed using Structured Analytical Model (SOWT-ANP). Findings and results showed.the most important effective factor on city-boundary relations is social factors with a mean of 3.55 and among weaknesses, Most affected were social weaknesses with a mean of 3.63 and among the opportunities examined, economic and managerial factors with a mean of 3.53 and Finally, they have the most impact on all types of threats, injuries and social threats with an average of 3.75. Also, the use of the method(F.ANP)in this study showed that the highest weight related to the threat factor was "management", which gained 7.9% of the final weight and took the first place. "Establishing economic, political and environmental security to deal with crises, attacks and ... (ST2)" is the most desirable strategy of deciding on the issue of zero value. And the strategy of "non-cooperation and interruption of cross-border relations with neighbors (WT1)" has been identified by experts as the worst strategy in this regard. Therefore, it can be said that among the factors (SWOT) "threats and challenges" in security and management dimensions is the most influential factor And the real gap between the "opportunities" is the key to improving the relationships between cities and territories. Also, from the standpoint of sustainable development management (institutional and structural) factors with the highest degree of importance and social, economic and environmental factors are ranked next.